The Role of Fathers in Religious Education for Children Age 5-6 Years: Peran Ayah dalam Pendidikan Agama bagi Anak Usia 5-6 Tahun - Dwiana Octafia (Chalim Journal of Teaching and Learning, 2025)
This study aims to explore the forms, meanings, and impacts of father involvement in the religious education of early childhood, specifically among children aged 5–6 years at TK Nilasari. It also analyzes the factors that either support or hinder such involvement. A qualitative case study approach was employed, with data collected through in-depth interviews with fathers, mothers, and teachers, as well as documentation of children's religious activities. Data analysis was conducted using NVivo software to organize and identify key themes systematically. The findings reveal that father involvement is manifested in various religious activities with their children, including guiding prayers, performing congregational prayers, reading prophetic stories, modeling religious practices, and utilizing Islamic digital media as educational tools. Supporting factors for father involvement include personal religious awareness, harmonious communication with the mother, enthusiastic responses from the child, flexible work schedules, and a supportive family environment. Conversely, inhibiting factors include work-related busyness, traditional gender norms that limit paternal roles in caregiving, limited understanding of religious pedagogy, and the lack of school initiatives to involve fathers in children's spiritual activities. Father involvement is shown to have a positive impact on the development of children's religious character and social skills. This study contributes to the growing body of literature on paternal roles in early childhood religious education, a topic that remains underexplored.